Implementasi Akuntansi Pesantren Sebagai Bentuk Transparansi Dan Akuntabilitas Pelaporan Keuangan Pondok Pesantren - Atieq Amjadallah A; Khanifah; Gus Hanifah Nuranisya (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2023)
IAI is working with Bank Indonesia, the Islamic Boarding School Accounting Guidelines are issued as a form of IAI and BI's partiality to empower Islamic boarding schools' economies to be able to present financial reports based on accounting standards in force in Indonesia. Reporting with integrity and quality can be achieved through financial preparation reports that refer to the Islamic Boarding School Accounting Guidelines. The purpose of this study is to determine the preparation of financial reports, to analyze the application of the Islamic Boarding School Accounting Guidelines, and to find out how transparent Assalafy Al Asror Islamic Boarding School is in its accountability for financial reporting. The type of research taken is descriptive qualitative with an intrinsic case study approach, namely a research effort with the aim of knowing more deeply about an event. Data collection procedures were carried out by means of observation, interviews, and document studies. This study resulted in (1) In compiling the financial reports of the Assalafy Al Asror Islamic Boarding School only reporting cash receipts and disbursements (2) Presentation of financial reports that were not in accordance with the explanation in the Islamic Boarding School Accounting Guidelines which the researchers then made recommendations for (3) Transparency and accountability that were not yet can be achieved due to several obstacles in implementing Islamic Boarding School Accounting Guidelines.